Mediated visibility, morality and children in tabloid discourse - Ndlovu, Khulekani (Centre for Film and Media Studies, 2021)
Media studies has recently witnessed an upsurge in theoretical and empirical work that investigates the moral-ethical implications of the mediation of suffering. The research focus has largely been limited to representations of distant suffering by global media to audiences in the Global North. Contrary to the above, this work focuses on the mediation of suffering by media in the Global South. This study is underpinned by the understanding that suffering is also a proximal (local) phenomenon and mundane (everyday) phenomenon. It is against this backdrop that this work uses the B-Metro tabloid's mediations of child abuse in Bulawayo, Zimbabwe as a case study. The study espouses a holistic view of mediation where mediation is the social circulation of meaning across the moments of production, text and reception. Roger Silverstone's concept of proper distance is used to evaluate the extent to which the BMetro's representations of child maltreatment are successful in engendering an ethic of care among its readership. Methodologically, the study triangulates focus group data about the context of production, with a textual analysis of the child abuse stories and focus group data about the reception of the same. Findings from the context of production point to an overreliance on legal, social and cultural elites for news about child abuse. Data shows that B-Metro journalists are torn between compassion and institutionalised compassion fatigue about child abuse. Findings also point to the prevalence of a gendered perception of child abuse among the journalists. Textual analysis data revealed that the editorial discourse identifies the ethic of care and the ethic of voice as being instrumental in the fight against child abuse. Further, the texts exhibit a patriarchal, gendered and heteronormative conception of child abuse. Reception data shows that it is more plausible to think of media users' responses as being located along a continuum whose range spans compassion fatigue and an ethic of care. A typology of witnessing is used to capture readers' responses to the mediations of child abuse. The tabloid genre was found to be simultaneously enabling and disabling the successful activation of an ethic of care. The thesis concludes by advancing a dialectical view of mediation that explores the equivalences and ambivalences between the moments of production, text and reception.